VD_FINDINFO Jug / 2024 / 59 vom 8. August 2023 - VD Tribunal cantonal (2023)
VIOL, CONTRAINTE SEXUELLE, ACTE D'ORDRE SEXUEL AVEC UN ENFANT, CONTRAINTEDROIT PÉNAL | 189 CP, 190 CP, 10 CPP (CH), 433 al. 1 CPP(CH)